Object Detection in Military & Space Image by Deep Learning with Convolutional Neural Network - Patil, Chitra J; Shinde, Swati V (International Journal of Computer Sciences and Engineering, 2025)
In recent years, the various Deep Learning architectures have been applied in fields such as speech recognition, natural language processing, and many more classification tasks, where they have usually undergoing the traditional methods. The motivation for such an idea is inspired by the fact that the human brain is organized in a deep architecture, with a given input percept represented at several levels of abstraction. Previous research has problems like – complex unstructured data of satellite images to be observed in short period of time & result is misjudged. So, it is difficult to obtain accurate result immediately. Therefore, proposed paper addresses need of Convolutional Neural Network (CNN) for automatic object detection in military & space image. As per study of CNN we conclude as it is for accurate classification of object from image